A Simple and Efficient Model to Determine the Photonic Parameters of a Photopolymerizable Resin Usable in 3D Printing. Issue 9 (21st May 2021) - Champion, Aymeric; Metral, Boris; Schuller, Anne‐Sophie; Croutxé‐Barghorn, Céline; Ley, Christian; Halbardier, Lucile; Allonas, Xavier
Abstract: This study provides insight into the relationship between the photochemical reactivity and the photonic parameters of an acrylate formulation usable in digital light processing (DLP) 3D printing. First the photoreactivity of riboflavin tetrabutyrate (RFT) used as a non‐toxic photoinitiator is assessed by laser flash photolysis in the absence and in the presence of an amine as co‐initiator. RFT alone is able to photopolymerize the acrylate formulation at a rate which is drastically increased when the co‐initiator is added. Then, the depth of light penetration (Dp) and the critical energy (Ec) to form a polymer film were measured and compared to those determined from the Bouguer‐Lambert‐Beer law for Dp and from the Stockmayer equation and photopolymerization experiments for Ec. A new proposed model is able to predict the in‐depth acrylate conversion within a printed part with a relatively low input of experimental parameters. Confocal Raman microscopy is used to discuss the effect of the photobleaching of RFT in the absence of co‐initiator on the photopolymerized films. Finally, it is shown that this formulation performs quite well for 3D printing with a resolution close to the best performance of the DLP printer. Abstract : A simple model is described which relates the photochemical reactivity of a photoinitiating system and a photopolymerizable bio‐based acrylate resin to the photonic parameters usable in 3D printing. This model can also predict the change in the conversion of the resin in‐depth, thereby explaining the heterogeneity in objects created through vat photopolymerization.